If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + -4) = x + 5x + 8 Reorder the terms: x(-4 + x) = x + 5x + 8 (-4 * x + x * x) = x + 5x + 8 (-4x + x2) = x + 5x + 8 Reorder the terms: -4x + x2 = 8 + x + 5x Combine like terms: x + 5x = 6x -4x + x2 = 8 + 6x Solving -4x + x2 = 8 + 6x Solving for variable 'x'. Reorder the terms: -8 + -4x + -6x + x2 = 8 + 6x + -8 + -6x Combine like terms: -4x + -6x = -10x -8 + -10x + x2 = 8 + 6x + -8 + -6x Reorder the terms: -8 + -10x + x2 = 8 + -8 + 6x + -6x Combine like terms: 8 + -8 = 0 -8 + -10x + x2 = 0 + 6x + -6x -8 + -10x + x2 = 6x + -6x Combine like terms: 6x + -6x = 0 -8 + -10x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '8' to each side of the equation. -8 + -10x + 8 + x2 = 0 + 8 Reorder the terms: -8 + 8 + -10x + x2 = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -10x + x2 = 0 + 8 -10x + x2 = 0 + 8 Combine like terms: 0 + 8 = 8 -10x + x2 = 8 The x term is -10x. Take half its coefficient (-5). Square it (25) and add it to both sides. Add '25' to each side of the equation. -10x + 25 + x2 = 8 + 25 Reorder the terms: 25 + -10x + x2 = 8 + 25 Combine like terms: 8 + 25 = 33 25 + -10x + x2 = 33 Factor a perfect square on the left side: (x + -5)(x + -5) = 33 Calculate the square root of the right side: 5.744562647 Break this problem into two subproblems by setting (x + -5) equal to 5.744562647 and -5.744562647.Subproblem 1
x + -5 = 5.744562647 Simplifying x + -5 = 5.744562647 Reorder the terms: -5 + x = 5.744562647 Solving -5 + x = 5.744562647 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + x = 5.744562647 + 5 Combine like terms: -5 + 5 = 0 0 + x = 5.744562647 + 5 x = 5.744562647 + 5 Combine like terms: 5.744562647 + 5 = 10.744562647 x = 10.744562647 Simplifying x = 10.744562647Subproblem 2
x + -5 = -5.744562647 Simplifying x + -5 = -5.744562647 Reorder the terms: -5 + x = -5.744562647 Solving -5 + x = -5.744562647 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + x = -5.744562647 + 5 Combine like terms: -5 + 5 = 0 0 + x = -5.744562647 + 5 x = -5.744562647 + 5 Combine like terms: -5.744562647 + 5 = -0.744562647 x = -0.744562647 Simplifying x = -0.744562647Solution
The solution to the problem is based on the solutions from the subproblems. x = {10.744562647, -0.744562647}
| 10h-7=9h-26 | | X=96+7x | | 42=6-2/3x | | 7/10d-21/10 | | 4x-70=12y+2 | | 4p^2-2-p=2-p | | 5x-7x=7 | | -3-12-5+2/3= | | m^4/2m^4 | | 2x/3-5=x-1 | | b/5+1/6=13 | | .25x-2.5=1x+1 | | 6k-1k=5k+10 | | 133=-3(7n+4)-2 | | 10d+9=-7+2(4d+3) | | 5x-2x+4=10 | | 1000(9x-10)=50(656+100x) | | 2(x-7)+x=3(x-6)+4 | | y-60=7x-35 | | (w-6)=3(w+1) | | -12/-4+12/6+3= | | 4x-5x=-4 | | 4x^2+2=402 | | 4y-(-10)=26 | | -6b+8=-8-2(4b+1) | | 5(1-2x)+5=80 | | 7x+-1=2x+5 | | -2x(7-y)+4=-4 | | 9+10(1+7a)= | | -3+4b= | | r=-4 | | -2x(7-y)+7=-4 |